2016
DOI: 10.1007/s00217-016-2727-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and geographical discrimination of Greek pine and thyme honeys based on their mineral content, using chemometrics

Abstract: correctly classified according to geographical origin. The correct prediction rates were 84.6 and 83.3 % for pine and thyme honeys, respectively, using the cross-validation method. Present results showed that selected minerals in combination with chemometrics may aid to the geographical differentiation of Greek honeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
6
25
0
Order By: Relevance
“…Preparation of honey samples for ICP-OES analysis and ICP-OES instrumentation and conditions are given in a previous study [ 10 ]. Twenty-four minerals were determined including Al, As, B, Ba, Be, Ca, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Mo, Ni, P, Pb, Sb, Si, Ti, Tl, V, and Zn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of honey samples for ICP-OES analysis and ICP-OES instrumentation and conditions are given in a previous study [ 10 ]. Twenty-four minerals were determined including Al, As, B, Ba, Be, Ca, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Mo, Ni, P, Pb, Sb, Si, Ti, Tl, V, and Zn.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, the great variability in honey chemical composition is closely related to botanical and geographical origins with regard to soil, specific vegetation, climate conditions, bee species, processing technologies, and honey extraction methods. Thus, these variations, that is, in the mineral content and/or physicochemical parameters of honey, offer a great opportunity for research related to its botanical or geographical discrimination (authentication), using supervised statistical techniques [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the category of 'oils': olive oil [22][23][24]. Other categories of 'seafood': scallops [25], eel [26], sea bass [27], clams [28], 'honey': thyme honeys [29], pine, and thyme honeys [30], commercial honey [31], [32] 'meat': [33], lamb (South Africa) [34], 'milk and dairy products': milk and cheese from buffalo [35], sheep milk [36] and others [37]. More specific, in the category of 'plant-crops and herbs', which is the category with the largest number of publications, there were articles with various analytical techniques for geographical origin authentication.…”
Section: Published Research For Geographical Origin Authentication Frmentioning
confidence: 99%
“…Results of this study showed that: (a) conventional physicochemical and color parameters, (b) mineral content, and (c) the combination of both using chemometrics may successfully differentiate the geographical origin of commercial thyme honey from different countries. In another article, Karabagias et al [30] investigated pine and thyme honeys produced in Greece. Conventional physicochemical and color parameters were determined using official methods of analysis.…”
Section: Published Research For Geographical Origin Authentication Frmentioning
confidence: 99%
“…Thyme honey with a pleasant aroma and taste is one of the most popular and widely used monofloral honeys globally (23). Studies on the thyme honey suggest that this honey is as significant as other dark honeys containing phenol, flavonoids and vitamin C, and has higher antioxidant properties than other honeys.…”
Section: Introductionmentioning
confidence: 99%